Correlation of motor control in the supine position and assistive device used for ambulation in chronic incomplete spinal cord-injured persons - Tang, S F; Tuel, S M; McKay, W B; Dimitrijevic, M R (American journal of physical medicine & rehabilitation, 1994)
Neurocontrol of movement after spinal cord injury (SCI) is often spared, but few studies have investigated the chronic incomplete SCI patient. Multichannel surface electromyography (SEMG) can describe characteristics of neurocontrol during a series of volitional and reflex events. The relationship of these neurocontrol characteristics to clinical function is incompletely described. This study, retrospectively, evaluated the relationship between neurocontrol patterns evoked by lower limb movement in the supine position and the assistive device used for ambulation in chronic, incomplete SCI persons. The records of 15 neurologically healthy (9 male, 6 female) and 36 incomplete SCI persons (27 male, 9 female) (C2-T10) were used. SEMG was recorded from both quadriceps, adductors, hamstrings, anterior tibialis and triceps surae muscles and displayed on a stripchart for analysis. SEMG patterns of activity recorded in the supine position during volitional, unilateral, multijoint (hip and knee flexion and extension) movement attempts were characterized, divided into seven groups and compared with the subjects' self-selected ambulation device (independent, cane, crutches, walker or nonambulatory). The neurocontrol patterns recorded in the supine position correlated well with the SCI subjects ambulatory assistive device. Marked decreases in motor unit output and/or loss of motor organization were found in the nonambulatory group. Coactivation of proximal muscles, poor timing of muscle activity and radiation of activity into contralateral muscles were also noted in subjects who required a walker or crutches. To a lesser degree, abnormal motor patterns were also noted in subjects who ambulated with a cane or independently.